1 - Democratization of Science and Biotechnological Development: Public Debate on GM Maize in South Africa - Mwale, Pascal Newbourne (Africa Development, 2021)
The Mandela government that came into power in 1994 made the democratiza- tion of science and technology a priority in post-apartheid South Africa. At- tendant ideas of Science Communication and Public Understanding of Biotech- nology have hitherto become currency in South Africa’s public sector drive towards the democratization of science. Democratization of science and tech- nology implies that the people, as non-experts, are an integral part of all delibera- tions on policy, regulation and control of science and technology, for example, in debates or controversies on issues arising from biotechnology. Democratiza- tion of science and technology is about the sociopolitical control of science and technology by the wider society. Science and technology must be controlled by the society at large because evil-minded groups of people can ill-use it to inflict harm on other groups of people. Moreover, certain unscrupulous and corrupt business entities can collude with the state and/or powerful and influential sociopolitical figures in societies to exploit and abuse indigenous scientific resources as well as endogenous modes of specialized scientific knowledge. On the latter, for example, they can evoke intellectual property rights (IPR) to patent resources that are not theirs historically. Thus, the ideal-type of democracy makes it imperative for the people of South Africa and of other societies in Africa to understand and actively participate in the development of science and tech- nology. This necessitates increasing scholarly attention to be given to questions of science communication and public understanding of science, arising at the intersection between science, society and politics in South and southern Africa. This paper discusses the role and importance of social movements in science communication and public understanding of biotechnology in South and southern Africa.